2020
DOI: 10.1155/2020/6548682
|View full text |Cite
|
Sign up to set email alerts
|

Bridge Seismic Damage Assessment Model Applying Artificial Neural Networks and the Random Forest Algorithm

Abstract: Earthquakes cause significant damage to bridges, which have a very strategic location in transportation services. The destruction of a bridge will seriously hinder emergency rescue. Rapid assessment of bridge seismic damage can help relevant departments to make judgments quickly after earthquakes and save rescue time. This paper proposed a rapid assessment method for bridge seismic damage based on the random forest algorithm (RF) and artificial neural networks (ANN). This method evaluated the relative importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Te most common method to improve the seismic performance of the continuous girder bridges is by installing multiple isolation devices. Researchers have performed substantial research on installing isolation bearings and viscous dampers for continuous beam bridges and obtained considerable research results [2][3][4][5][6][7][8]. Kelly and Eidinger [9] and Kelly [10] proposed the system theory and design method of laminated rubber bearing and performed tensile test research on their approach.…”
Section: Introductionmentioning
confidence: 99%
“…Te most common method to improve the seismic performance of the continuous girder bridges is by installing multiple isolation devices. Researchers have performed substantial research on installing isolation bearings and viscous dampers for continuous beam bridges and obtained considerable research results [2][3][4][5][6][7][8]. Kelly and Eidinger [9] and Kelly [10] proposed the system theory and design method of laminated rubber bearing and performed tensile test research on their approach.…”
Section: Introductionmentioning
confidence: 99%
“…However, regardless of the type of isolation bearings adopted, a large relative displacement must be applied to accomplish the ideal damping e ect [4,5]. In recent years, sure researchers have conducted systematic studies on lock-up devices; then, lock-up connections cannot e ectively reduce the impact of seismic activity on low-pier continuous-girder bridges [6][7][8][9][10]. Moreover, owing to cost and late maintenance, there are not many applications in practical engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Mangalathu et al (2019) and Mangalathu and Jeon (2019), used random forest models to establish the seismic fragility curves for California bridges, and then proposed a method for rapid damage state assessments using ML techniques. Jia et al (2020) sorted the importance levels of the specific characteristics and identified the seismic damages to the bridges following the Wenchuan earthquake according to the ML models. Xu et al (2020) applied ML techniques to predict building structure types, and provided a method for obtaining structural types for a city-scale seismic damage simulation.…”
Section: Introductionmentioning
confidence: 99%